A Study of Scheduled Caste and Scheduled Tribe Women of Ananthapuramu District Women Empowerment through Panchayat Raj: Challenges and Opportunities for Women Empowerment through Panchayat Raj (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The development in the seventy-third Constitutional Amendment of Panchayati Raj Institutions (PRIs), based on Independence provisions on the vulnerable sections reservations of women in particular. Various studies were mentioned to explain, on the contrary, the influence of the constitutional amendment on the empowerment of women in the 73rd constitutional amendment of 1993. True, reservations for women in PRIs have provided enormous opportunities for the advancement of women, especially women in the disadvantaged sectors. But a lot of hurdles and problems exist. Ensuring that the actual power levers are generally still in male hands, has the entrenched patriarchal system and thinking, the rigorous caste division and endemic discrimination in rural life, vast female iliteracy and female dependency on men. Research has shown that a few countries in the south and west are far more advanced than those of the north and those of the east. Bihar has offered 50 percent quota for women in PRIs and has created a big impact on empowerment, however not very good in terms of other factors. The obstacles, as mentioned before, must be eliminated urgently to provide genuine empowerment to women.